1997
DOI: 10.1002/(sici)1097-0088(199708)17:10<1055::aid-joc180>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Indian summer monsoon with the northern hemisphere mid-latitude circulation

Abstract: The association between the mid–latitude circulation and rainfall over the Indian region on an intraseasonal time–scale is investigated by considering 11 years (1974–1984) of Northern Hemisphere 500 hPa geopotential heights and rainfall data for the Indian summer monsoon months June through to September. On the basis of extensive correlation analysis between the geopotential heights and rainfall, it is seen that three regions over the mid–latitudes, the Manchurian region, the Algerian region and the Caspian se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
79
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 26 publications
9
79
0
Order By: Relevance
“…Understanding the variability of the ISMR on decadal to multidecadal timescales is essential for adequate planning of farming and relevant infrastructure development, and for adapting to the consequences of future climate change (Krishnamurthy et al 2014;Joshi and Rai 2015). Other than on inter-annual timescales the ISMR varies on decadal to multi-decadal timescales as various studies identified the presence of a ~60-year cycle in it (see, Mooley and Parthasarathy 1984;Verma et al 1985;Kripalani et al 1997;Krishnamurthy and Goswami 2000;Goswami 2006a;Zhou et al 2009a). The potential factors which cause the decadal to multi-decadal scale variability of the ISMR are Pacific decadal oscillation (PDO), Atlantic multi-decadal oscillation (AMO), and external climate forcings i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the variability of the ISMR on decadal to multidecadal timescales is essential for adequate planning of farming and relevant infrastructure development, and for adapting to the consequences of future climate change (Krishnamurthy et al 2014;Joshi and Rai 2015). Other than on inter-annual timescales the ISMR varies on decadal to multi-decadal timescales as various studies identified the presence of a ~60-year cycle in it (see, Mooley and Parthasarathy 1984;Verma et al 1985;Kripalani et al 1997;Krishnamurthy and Goswami 2000;Goswami 2006a;Zhou et al 2009a). The potential factors which cause the decadal to multi-decadal scale variability of the ISMR are Pacific decadal oscillation (PDO), Atlantic multi-decadal oscillation (AMO), and external climate forcings i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also pointed out that anomalies at higher latitudes are considered to influence the variations in the Asian monsoon (Kripalani et al, 1997;Bansod et al, 2005;Ding and Wang, 2007;Fujinami and Yasunari, 2009;Krishnan et al, 2009). A study by Kripalani et al (1997) showed that the west Pacific teleconnection pattern in the mid-troposphere is significantly related to the ISMR.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kripalani et al (1997) showed that the west Pacific teleconnection pattern in the mid-troposphere is significantly related to the ISMR. Also Bansod et al (2005) pointed out that mid-tropospheric height over the eastern tropical Pacific Ocean during winter plays an important role in modulating the ISMR.…”
Section: Introductionmentioning
confidence: 99%
“…Walker, 1924;Thapliyal and Kulshrestha, 1992;Krishna Kumar et al, 1995;Kripalani et al, 1997;Webster et al, 1998;Krishamurthy and Goswami, 2000;Hu et al, 2005). However, the relationships of the parameters with AISMR are not robust and undergo changes over the decades (Rajeevan, 2002).…”
Section: Introductionmentioning
confidence: 99%